Intestinal Parasitic Infections in Renal Transplant Recipients - EB Kia (Iranian Journal of Parasitology, 2007)
Background: Organ transplant recipients can experience serious diseases from infections due to emerging and reemerging parasitic infections. This study was carried out to evaluate the prevalence of intestinal parasites among renal transplant re-cipients of Iran. "nMethods: This cross-sectional study was conducted from June 2003 to August 2004 on renal transplant recipients in Iran. A total of 706 fecal samples obtained from randomly selected population originated from all over Iran. Patient's information was recorded in a questionnaire before sampling. A sample of stool was taken from each person. Direct wet smear exami-nation, formalin-ether concentration, Ziehl-neelsen staining, and agar plate culture were done for each sample. "nResults: Totally 32 patients (4.5%) were positive for parasitic infections. In searching for emerging parasitic infections, the most prevalent parasites were found to be Blastocystis hominis, Giardia lamblia and Entamoeba coli, respectively. The merely ova which were seen were related to Hymenolepis nana. With investigation of healthy control, no significant differ-ence was found between transplanted and normal population. "nConclusion: The population showed controlled rate of intestinal infections probably due to regular awareness concerning risks of opportunistic infections; albeit regular surveillance through routine examination of stool samples for parasites seems considerably advantages the transplant recipient patients.